With a 'spring' in your step. (2nd April 2022) - Harries, Judith
Abstract : The fifth article in this series, exploring traditional nursery rhymes as a resource and inspiration for activities, focuses on literacy. These include: repeating simple rhymes, recognising and reading CVC (consonant, vowel, consonant) words, using writing frames and enjoying spring rhymes.